Symptomatic Clitoral Neuroma within an Epidermal Inclusion Cyst at the Site of Prior Female Genital Cutting - Dani Zoorob; Kristrun Kristinsdottir; Thomas Klein; Sonyoung Seo-Patel (Case Reports in Obstetrics and Gynecology)
Background. Clitoral neuromas occurring after female genital mutilation/cutting (FGM/C) can vary in presentation and may require surgical management. Case. A 39-year-old East African female with a history of FGM/C presented during pregnancy with a progressively enlarging mass and worsening periclitoral pain. Postpartum surgical excision restored cosmesis and resolved the discomfort with pathology confirming the presence of a neuroma within the epidermal inclusion cyst. Conclusion. We present the first published case of a symptomatic clitoral neuroma within an epidermal inclusion cyst. This unique pathology demonstrates that complications of female genital cutting can present in complex and varied ways. Considering the prevalence of FGM/C and increasing rates of emigration from countries in which FGM/C is performed, complex clitoral neuromas are an important long-term complication which providers in Africa or internationally must be aware of.